Pykrete is the frozen composite material of the World War II - O. V. Kovalev; M. N. Andreev; V. V. Rice (Лëд и снег)
During the war, government of the allies considered the construction of ice structures converted from artificial icebergs into aircraft carriers. The idea to use ice for construction of floating aerodromes, or giant aircraft carriers, was launched by Geoffrey Pyke, and then was developed in a project called «Habbakuk». Aircraft carriers, made of ice, had to work for a long period of time at temperatures of water and air, resulting in rapid destruction of the structure of ordinary ice. The ice in its pure form is unsuitable for any engineering form therefore the experiments on reinforcement of ice were undertaken. New form of ice engineering was based on the type of reinforcement patterns of ice and coating it with an insulating material, which would greatly reduce the influence of melting due to the temperature of the ambient air. After tests with different substances and proportions, it was found that the mixture of ice with wood pulp, amounting to about 14%, gives the best result of reinforcement. Proposed dimensions of «Habbakuk» were 610 m (2000 ft) long, 90 m (300 feet) in width and a height of 60 m (200 ft). In 1943, on the surface of the lake Patricia a reduced model to test the viability of the project was constructed. Development of improved long-range aviation, the airbase in Iceland and other technological advances contributed to the successful elimination of the threat from submarines, so the project had been suspended. The technology of strong ice structures invented during the World War II time can still have practical applications today.